The stigma associated with bereavement by suicide and other sudden deaths: A qualitative interview study. (February 2018) - Pitman, Alexandra L.; Stevenson, Fiona; Osborn, David P.J.; King, Michael B.
Abstract: Quantitative studies have found that suicide bereavement is associated with suicide attempt, and is perceived as the most stigmatising of sudden losses. Their findings also suggest that perceived stigma may explain the excess suicidality. There is a need to understand the nature of this stigma and address suicide risk in this group. We aimed to describe and compare the nature of the experiences of stigma reported by people bereaved by suicide, sudden unnatural death, and sudden natural death, and identify any commonalities and unique experiences. We conducted a population-based cross-sectional survey of 659, 572 staff and students at 37 British higher educational institutions in 2010, inviting those aged 18–40 who had experienced sudden bereavement of a close contact since the age of 10 to take part in an on-line survey and to volunteer for an interview to discuss their experiences. We used maximum variation sampling from 1398 volunteer interviewees to capture a range of experiences, and conducted individual face-to-face semi-structured interviews to explore perceptions of stigma and support. We continued sampling until no new themes were forthcoming, reaching saturation at n = 27 interviews (11 participants bereaved by suicide). We employed thematic analysis to identify any distinct dimensions of reported stigma, and any commonalities across the three groups. We identified two key themes: specific negative attitudes of others, and social awkwardness. Both themes were common to interviewees bereaved by suicide, sudden unnatural death, and sudden natural death. All interviewees reported the experience of stigmatising social awkwardness, but this may have been experienced more acutely by those bereaved by suicide due to self-stigma. This study provides evidence of a persistent death taboo in relation to sudden deaths. There is potential for anti-stigma interventions to reduce the isolation and social awkwardness perceived by people bereaved suddenly, particularly after suicide loss. Highlights: Explores stigma after suicide, unnatural deaths and sudden natural deaths. First qualitative study internally comparing these three groups' experiences. All three groups described stigmatising social awkwardness. The death taboo in relation to sudden deaths is particularly marked after suicide.